La gouvernance participative des forêts publiques : L’Ontario et le Québec, des chemins parallèles ? - Guy Chiasson; Catalina Gonzalez; Édith Leclerc (Territoire en Mouvement)
Canadian provincial’s forest policies reflect the transition dynamic from a hierarchical governance to a "multilevel governance" (Pülzl and Rametsteiner, 2002), meaning that they open spaces to new actors. Canada's forest sector has been the core of national economic development, being a lever for regional development, particularly in the provinces of Ontario and Quebec. Our paper would like to emphasize the points of convergence and divergence between participatory governance mechanisms established in each province in forest policy decision making. Our analysis suggests that several similarities transcend this new generation of governance, but it takes place in specific institutional contexts that modulate participatory forms. In the cases studied, two distinct trajectories of participatory governance have been identified : the territorialization of participation in the case of Quebec and the reconstruction of provincial governance in Ontario. This comparative analysis helps to reframe some of the terms of debate in regard to the theories and forms of participatory governance.